ANALISIS KONSEP, ERGONOMI, DAN PENCAHAYAAN PADA RUANG KERJA KANTOR DITJEN BIMAS BUDDHA KEMENTERIAN AGAMA, JAKARTA: Analysis of Concepts, Ergonomics, and Lighting in the Office Workspace of the Directorate General of Buddhist Community Guidance, Ministry of Religious Affairs, Jakarta - Jelly Tan; Fathya Aulia Shabrina; Shofiyah Hisyam Lenggana; Resky Annisa Damayanti (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2023)
The use of interior design has become a complement to a main factor of building aesthetics. Apart from prioritizing aesthetics, interior design also prioritizes comfort and harmony to make the design more efficient and help the user's productivity. This research focuses on interior concepts, ergonomics studies and lighting in the workspace of the Buddhist Ministry of Religion which currently feels unfulfilled, such as furniture and circulation that are currently not in accordance with ergonomics studies which causes workers to complain because of discomfort while working. This research aims to produce a comfortable and efficient workspace for users. Therefore, a descriptive qualitative method is used in this study to obtain data to improve interior concepts, ergonomics studies and lighting in workspaces for a long period of time. The data obtained are interior concepts, ergonomics, and lighting in the work space which are still lacking and can be further developed to create comfort for workers. Keywords: workspace, the Ministry of Buddhism office, interior concept, ergonomic studies, lighting